Pengaruh Sosial Ekonomi Orangtua, Lingkungan Sosial dan Aktualisasi Diri Siswa Terhadap Minat Siswa Melanjutkan Pendidikan Keperguruan Tinggi (Studi Kasus di SMAN 1 Kayu Tanam Kab. Padang Pariaman) - Rika Verawati; Desi Areva; Jimi Ronald (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2018)
This study aims to analyze: The influence of social ekonorang parents, social environment, self-actualization of student interests SMA Negeri 1 Kayu Tanam. sampling technique that is with Stratified Random Sampling by using Neyman allocation formula. The technique of data analysis using multiple linear regression analysis by doing t test and F test. The results showed: (1) variable socioeconomic status of high income parents obtained coefficient value 0.423, t value counted 3.797> ttable of 1.689 with significant value 0.000 < α = 0.05, meaning Ha is accepted and H0 is rejected. Socioeconomic status of low income parents obtained coefficient value 0,422 and tcount of 3,921> ttable equal to 1,675 with significant value 0,000 <α = 0,05, meaning Ha accepted and H0 rejected. (2) social environment variable obtained tcount of 3,165> ttable equal to 1,689 with significant value 0,002 <α = 0,05, mean Ha accepted and H0 rejected so can be said that there is positive influence and partially significant between social environment to interest continue education to college in SMA N 1 Kayu Tanam. (3) Variable aktualiasasi high-income parents obtained t count value of 4.144> ttable of 1.689 with significant value 0,000 <α = 0.05, means Ha accepted and H0 rejected so it can be said that there is a positive influence and partially significant between the actualization self towards the interest of continuing education to college in SMA N 1 Kayu Tanam. (4) Social economic variable of parent, social environment and self actualization simultaneously give positive and significant influence to student interest to continue education to university in SMA Negeri 1 Kayu tanam with value Fhitung 24,874> Ftabel 2,64 and significant value 0,000 <α = 0.05. This means H0 is rejected and Ha accepted. As for the low income level Fcount of 31.082> Ftable 2.56 and significant value 0,000 <α = 0.05. This means H0 is rejected and Ha accepted.